Defending the past by challenging the future: spatial and institutional path dependencies in the Naples port-city region - Paolo De Martino (Regional Studies, Regional Science, 2020)
Historical paths matter in port-city regions. Here, spatial patterns and governance arrangements are path dependent to the point that once certain paths have been established, these become hard to change. This defines a condition of institutional inertia that plays a significant role in preventing any form of spatial change. Naples is an exemplar of how different actors have historically developed their own routines and planning tools, resulting in the spatial and governance separation still visible today. How do path dependencies influence the port–city (and regional) relationship we are experiencing today? Nowadays, ports operate in an increasingly changing environment where spatial and economic developments can be better understood as the results of actors’ interactions across different scales. In order to cope with global urgencies, such as energy, economic and societal transition, European infrastructure policies are driving many port authorities towards infrastructural integration and governance cooperation. This offers significant opportunities to improve relations among ports, but it mostly leaves out the interconnections with cities and larger regions. Moreover, it also challenges consolidated beliefs and planning cultures which have planned ports and cities as disconnected entities, at least since industrialization. In Naples, local and national authorities find it difficult to define a sustainable consistency of interests. Today, the Central Tyrrhenian seaport system is the new institutional umbrella overseeing the three main ports of the region: Naples, Castellammare di Stabia and Salerno. This paper investigates whether this new governance entity results in either an opportunity for change or a reinforcement of existing path dependencies.